Nursing diagnoses and interventions in mental health used in hospital admissions units: integrative Review / Diagnósticos e intervenções de enfermagem em saúde mental utilizados em unidades de internação hospitalares: revisão integrativa - Nathália Duarte Bard; Isadora Olizsewski Feijó; Jaqueline Ramires Ipuchima; Adriana Aparecida Paz; Graciele Fernanda da Costa Linch (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: The study’s purpose has been to identify nursing diagnoses and interventions used in hospital inpatient units related to mental health care. Methods: It is an integrative literature review that was performed in the PubMed, Scopus, and Web of Science databases, over the period from 2014 to 2018. Nine articles make up the study sample. Results: Mental health nursing diagnoses were grouped into related feelings: anxiety, fear, sadness, aggression, stress, denial, and family relationships. The interventions were related to cares as follows: clarify the treatment, be aware of physical and emotional risks, stimulate leaving the room, provide guidance on sleep hygiene, include family members in the treatment, promote and allow choices when possible, avoid physical and mental exhaustion of the patient, provide positive feedback on coping, provide emotional support, promote cognitive stimuli, guide appropriate behavior, perform active listening and mediate interpersonal conflicts. Conclusion: There was a shortage of studies addressing this matter.